3D‐printed mechanical metamaterials with high energy absorption - Yuan, Shangqin (2020)
Recently, 3D metamaterials have been achieved with inaccessible mechanical properties in natural materials such as negative Poisson's ratio, stiffness, and thermal expansion coefficient. While most of the developed metamaterials are with engineerable deformation evolution of structures, few studies have revealed their potential in energy absorption due to the limited mechanical properties of 3D‐printed constituent materials and inevitable structural defects induced by the manufacturing process. Herein, an approach is proposed for creating 3D metamaterials of auxetic composite lattices via laser‐sintering of carbon nanotubes reinforced nanocomposites, which provide a platform for the design and manufacturing of systems with programmable energy absorption capability. The optimization of constituent material and structural design enables the improvement of energy absorption performance across multiple scales. The energy absorption capacity of auxetic metamaterials was exponentially scaled with the relative density with the order of 2.5–3. The rationally topologized auxetic metamaterials exhibit a combination of high specific densification strength (0.0195 MPa kg−1 m−3), ultrahigh energy absorption capacity (6.29 MJ m−3), and excellent specific energy absorption (20.42 J g−1). Impressively, this group of auxetic metamaterials possesses the advantageous specific energy absorption approaching that of titanium alloy foams as well as over a broad range of materials including plastic foams, aluminum alloy foams, and other 3D‐printed lightweight structures.